Implementasi Konsep “Reborn: Experiencing Traditional Beliefs of Indonesian Archipelago” pada Interior Museum Aliran Kepercayaan di Yogyakarta - Abisag Elladora Hadiasali; Ronald Hasudungan Irianto Sitinjak; Linggajaya Suryanata (Intra, 2018)
Indonesia is a multi-religious country and various traditional beliefs that should be known by people as nation’s cultural richness, so that people could react and behave wiser in the society. Interior Design of Traditional Beliefs Museum in Yogyakarta offers an educational facility in the form of a museum that will help the people of Indonesia know more about the traditional beliefs of Indonesia. The design method used is the adoption of the design thinking scheme according to Jeroen de Groot namely Discover, Describe, Ideate and Prototype. Those design methods are the steps taken to find the right design solution through a design concept. The design concept chosen using the theory of cultural approach by Koentjaraningrat includes mentifact, sociofact, and artifact. These three aspects of cultural manifestation are translated and reprocessed to find a good design concept which is,